UJI PERFORMANSI ALAT DESTILASI UNTUK PEMURNIAN MINYAK DARI LIMBAH PLASTIK - Sirun, Artian; Priyono, Priyono; Bawano, Franklin; Pinangkaan, Niko (Otopro, 2023)
In everyday life the use of plastic materials is very dominant. The use of this plastic material from year to year has greatly increased, which has resulted in an increase in plastic waste. Various parties have conducted research to reduce plastic waste into something that can have added value, including converting plastic waste into alternative energy sources in the form of fuel. Handling of plastic waste can be done by recycling it by heating it in a reactor so that it becomes liquid oil, then the oil is purified using a distillation apparatus. This study aims to determine the performance of oil refining distillation equipment from the processing of Low Density Polyethylene (LDPE) plastic waste which can be used as fuel. The research method used is the performance test for refining oil from the processing of plastic waste which is heated with a distillation apparatus. Testing the plastic oil purification distillation apparatus was carried out 5 times, the test was carried out by means of each oil being put into the reactor totaling 3,500ml each time of testing, from the observations it showed that the results of tests 1 to 5 produced refined oil 1 = 1,592ml, 2 = 1.627ml, 3 = 1.609ml, 4 = 1.616ml, 5 = 1.319ml. The total amount of refined oil is: 7,768ml and the average temperature of the reactor is 184.6oC.